Virtualização de funções de rede em nuvem para instituições públicas - Gama Junior, Lucio da Silva (2017)
Network Function Virtualization (NFV) is a new trend in the network, where network functions are shifting from custom hardware devices to software deployments in virtual machines hosted on common hardware. This is due to the fact that in a traditional network, all functions are implemented in specific hardware and software, employing proprietary technology, difficult interoperability, configuration and operation, rendering it inadequate to meet the increasing demands of the Internet, which transformation of its infrastructure. NFV and cloud computing are complementary technologies that offer new solutions for designing, building and operating networks, allowing the coexistence of multiple, now virtual, networks on the same physical infrastructure. Backed by the benefits of cloud computing, networks can be organized more flexibly, with programmability and dynamism in their configurations. The objective of this work is to propose a strategy to virtualize network functions in a cloud environment, thus allowing organizations, especially public, to focus on this work, to take advantage of the paradigms that NFV and cloud computing can provoke in the infrastructure of their Data Centers. In order to do so, a cloud experimentation environment was built in order to provide computer network testing, thus preventing those tests in an active network and in production, compromising its normal operation. In this work, we detail the deployment of an open source cloud computing platform, OpenStack, how it can be used to implement the NFV, and how both can contribute to the creation of solutions able to meet the demands of traditional network infrastructures . To validate the experiment environment, a case study was carried out of the migration of a traditional network to an NFV network using the IPv4 and IPv6 protocols in a network environment of public institutions. The results obtained showed that the environment created is an important tool for conducting experiments that allow network administrators to plan, for example, the transition period and coexistence of these protocols, allowing that this change in computer networks can occur way.